# Find and correct the errors in the statement. (y - 3)^{2} = y^{2} - 9

**Solution:**

An equation is a mathematical statement with an 'equal to' symbol between two algebraic expressions that have equal values.

Given,

4(x - 5) = 4x - 5

Solving LHS we get,

(y - 3)^{2}

= (y)^{2} - 2(y)(3) + (3)^{2} [Using identity (a - b)^{2} = a^{2} - 2ab + b^{2}]

= y^{2} - 6 y + 9

But, RHS = y^{2} - 9

Thus, L.H.S ≠ R.H.S

The correct statement is (y - 3)^{2} = y^{2} - 6 y + 9

**☛ Check: **NCERT Solutions for Class 8 Maths Chapter 14

**Video Solution:**

## Find and correct the errors in the statement. (y - 3)² = y² - 9

Class 8 Maths NCERT Solutions Chapter 14 Exercise 14.4 Question 11

**Summary:**

Find and correct the errors in the statement: (y - 3)^{2} = y^{2} - 9. The correct statement is (y - 3)^{2} = y^{2} - 6 y + 9.

**☛ Related Questions:**

Math worksheets and

visual curriculum

visual curriculum